Critical appraisal of 3-monthly paliperidone depot injections in the treatment of schizophrenia - Carpiniello B; Pinna F (Dove Medical Press, 2016)
Bernardo Carpiniello, Federica Pinna Department of Public Health, Clinical and Molecular Medicine – Psychiatry Research Unit and Psychiatric Clinic, University Hospital, Cagliari, Italy Aims: Three-monthly injections of paliperidone palmitate (PP-3M) represent a new and recently introduced long-acting antipsychotic therapeutic option. This review focuses on available data relating to the efficacy and safety of PP-3M and its position in the current therapeutic scenario.Method: An analysis of PubMed, Scopus, and ISI Web of Knowledge databases was conducted, and all available papers on PP-3M, including poster presentations, were selected and considered for the purpose of the present review. Findings: to date, three full papers have been published, the first, a Phase 1 randomized, open label study investigating the pharmacokinetics, safety, and tolerability of the drug; the second, a Phase 3 double blind study vs placebo focusing on efficacy and tolerability; and the last relating to the practical use of PP-3M. The five posters identified describe data reported in the above-cited papers. Overall, the pharmacokinetic findings obtained in these studies highlight the feasibility of administering PP-3M on a 3-monthly basis, subsequent to the administration of four 1-monthly injections of PP at doses 3.5 times higher than the stabilized dose of 1-monthly injections of PP (ie, 175, 300, 450, and 525 mgs). The published studies highlight a significantly longer time to relapse compared to placebo, and significantly better results compared to placebo for all secondary end-points (Positive and Negative Syndrome Scale, Clinical Global Impression-Severity Scale, Personal and Social Performance Scale scores), in addition to reasonably good safety and tolerability profiles.Conclusion: PP-3M emerges as a potential candidate for use as a first-line long-acting agent in the maintenance treatment of patients with schizophrenia. Further studies should however be conducted to confirm this expectation. In view of its efficacy, tolerability, and safety, together with the longer timespan between injections, PP-3M currently represents one of the best available options, and may contribute towards addressing the issue of poor adherence, even in early psychosis. Keywords: long-acting antipsychotics, 3-monthly paliperidone palmitate, efficacy, safety, pharmacokinetics, schizophrenia